Odpowiedzi

2010-02-16T19:26:19+01:00
A) c(b+3)+c = cb+3c+c=cb+4c
b) b(b-4)+3b = b²-4b+3b=b²-b
c) 2a(a-2b)+5 = 2a²-4ab+5
d) -0,5(8x + 12y - 6)= 4x-6y+3
3 2 3
2010-02-16T19:31:41+01:00
A.)c(b+3)+c =cb + 3c+c=4c + cb
b.)b(b-4)+3b = b² -4b +3b= b² - b
c.)2a(a-2b)+5=2a² -4ab +5
d.)-0,5(8x + 12y - 6) =-4x-6y + 3

proszę!!
w podpunkcie b.) nie wiadomo gdzie kończy się nawias!!!
5 3 5
Najlepsza Odpowiedź!
2010-02-16T19:37:29+01:00
Cześć !

a) c*3b+c ( * razy) redukcja : 2c * 3b

b.)b(b-4)+3b = b² -4b +3b= b² - b
c.)2a(a-2b)+5=2a² -4ab +5
d ) -0,5(8x + 12y - 6)= 4x-6y+3
Licze na Najj ;*
5 2 5